Magnetic resonance imaging as a predictor of pathologic response in patients treated with neoadjuvant systemic treatment for operable breast cancer1. Issue 10 (21st February 2013) - De Los Santos, Jennifer F.; Cantor, Alan; Amos, Keith D.; Forero, Andres; Golshan, Mehra; Horton, Janet K.; Hudis, Clifford A.; Hylton, Nola M.; McGuire, Kandace; Meric‐Bernstam, Funda; Meszoely, Ingrid M.; Nanda, Rita; et al.
Abstract BACKGROUND: Increased pathologic complete response (pCR) rates observed with neoadjuvant chemotherapy (NCT) for some subsets of patients with invasive breast cancer have prompted interest in whether patients who achieved a pCR can be identified preoperatively and potentially spared the morbidity of surgery. The objective of this multicenter, retrospective study was to estimate the accuracy of preoperative magnetic resonance imaging (MRI) in predicting a pCR in the breast. METHODS: MRI studies at baseline and after the completion of NCT plus data regarding pathologic response were collected retrospectively from 746 women who received treatment at 8 institutions between 2002 and 2011. Tumors were characterized by immunohistochemical phenotype into 4 categories based on receptor expression: hormone (estrogen and progesterone) receptor (HR)‐positive/human epidermal growth factor receptor 2 (HER2)‐negative (n = 327), HR‐positive/HER2‐positive, (n = 148), HR‐negative/HER2‐positive, (n = 101), and triple‐negative (HR‐negative/HER2 negative; n = 155). In all, 194 of 249 patients (78%) with HER2‐positive tumors received trastuzumab. Univariate and multivariate analyses of factors associated with radiographic complete response (rCR) and pCR were performed. RESULT: For the total group, the rCR and pCR rates were 182 of 746 patients (24%) and 179 of 746 patients (24%), respectively, and the highest pCR rate was observed for the triple‐negative subtype (57 of 155 patients; 37%) and the HER2‐positive subtype (38 of 101 patients; 38%). The overall accuracy of MRI for predicting pCR was 74%. The variables sensitivity, negative predictive value, positive predictive value, and accuracy differed significantly among tumor subtypes, and the greatest negative predictive value was observed in the triple‐negative (60%) and HER2‐positive (62%) subtypes. CONCLUSIONS: The overall accuracy of MRI for predicting pCR in invasive breast cancer patients who were receiving NCT was 74%. The performance of MRI differed between subtypes, possibly influenced by differences in pCR rates between groups. Future studies will determine whether MRI in combination with directed core biopsy improves the predictive value of MRI for pathologic response. Cancer 2013. © 2013 American Cancer Society.